2003
DOI: 10.3319/tao.2003.14.1.41(a)
|View full text |Cite
|
Sign up to set email alerts
|

Annual and Semi-annual Variations of the Observed foF2 in a High Solar Activity Year

Abstract: By the Fourier series expanding method, the observed F2 layer critical frequencies (foF2) globally over 70 stations in a high solar activity year of 1958, are used to analyze the annual and semi-annual variations of foF2, and the world wide distribution features of their amplitude and phase in daytime and nighttime are studied in detail. The results for foF2 annual and semi-annual variation are summarized as follows. The midnight (2:00 LT) foF2 annual variations are noticeable in both hemispheres at mid-high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
2
7
0
2
Order By: Relevance
“…At night the semiannual anomaly is found during high solar activity and the larger values are located at mid to low geomagnetic latitudes with maximum values also recorded in the South American region. Similar conclusions were reached by Li and Yu [2003].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At night the semiannual anomaly is found during high solar activity and the larger values are located at mid to low geomagnetic latitudes with maximum values also recorded in the South American region. Similar conclusions were reached by Li and Yu [2003].…”
Section: Discussionsupporting
confidence: 86%
“…This causes the variation of the amplitude of the ionospheric equatorial anomaly through a fountain effect and this process induces the semiannual variation of N m F 2 at low latitude. The semiannual variations appear around the globe in daytime, and except in low-latitude regions and in South America sector, there is no obvious semiannual variation of N m F 2 in the nighttime [Li and Yu, 2003]. The amplitude of this variation has close relationship with the solar activity (larger values in maxima of solar activity).…”
Section: Introductionmentioning
confidence: 91%
“…Ma et al (2003) suggested that the semiannual variation of the diurnal tide in the lower thermosphere induces the semiannual variation of the amplitude of the equatorial electrojet, this causes the variation of amplitude of ionospheric equatorial anomaly through fountain effect and this process induces the semiannual variation of the low latitude NmF2. The semiannual variation appears around the globe at daytime, and except in low latitude region and in South American sector (Li and Yu, 2003) there is no obvious semiannual variation of NmF2 in the nighttime. The amplitude of this variation has close relationship with the solar activity, they have asymmetrical structures between the two hemispheres (larger at the Northern Hemisphere) and they have longitude difference (Ma et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some phenomena that were called anomalies in the early days of ionospheric exploration and have remained as such until the present. Two of the most widely known [see Fuller-Rowell, 1998;Rishbeth, 1998Rishbeth, , 2000Li and Yu, 2003;Mendillo et al, 2005] of these are (1) the semiannual anomaly, which produces larger f o F 2 values for equinoxes than for solstices; and (2) the annual anomaly (also called the annual asymmetry), which is described by a larger f o F 2 value during the December than during the June solstice (larger than the 7% that would be expected considering the change in the Sun-Earth distance). Another manifestation of the annual anomaly is the so-called winter anomaly [Appleton, 1938]: f o F 2 values measured during June over the Northern Hemisphere that are actually lower than (or comparable to) the December values, which is in opposition to the accepted dependence on the Sun's zenith angle.…”
Section: The Semiannual and Annual Anomaliesmentioning
confidence: 99%
“…The first reports concerning these so-called anomalies of the electron concentration in the upper atmosphere date back to the 1930s, to the pioneering works by Berkner et al [1936] and Appleton [1938]. Since then several authors have proposed different approaches to understanding, modeling, and predicting these anomalies [Fuller-Rowell, 1998;Rishbeth, 1998Rishbeth, , 2000Li and Yu, 2003;Mendillo et al, 2005]. However, the processes seemed to be so complex that no unique theory was able to model both effects, and many early theories could only partially explain one or the other.…”
Section: Introductionmentioning
confidence: 99%